MATERNAL ANXIETY AND DEPRESSION IN THIRD-TRIMESTER INTRAUTERINE FETAL DEATH: A CASE REPORT - Ainun Ganisia (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Intrauterine Fetal Death (IUFD) is the death of the fetus in the womb that causes the mother to feel traumatized and at risk of becoming anxious or depressed. IUFD is usually included in the stillbirth rate. The number of stillbirths in 2017 in Indonesia is around 13/1.000 live births. Objective: To evaluate and give initial support for anxiety and depression in maternal condition due to her IUFD experience. Methods: Evaluated case by questionnaire of HARS for assessing the level of maternal anxiety and HDRS questionnaire for determining the depression of maternal. Results: Total score of HARS is 13 and the HDRS score is 12, which categories of the mother are mild anxiety and mild depression. Conclusion: Early detection can help the maternal psychological problem in the early phase. As long as the case can still be resolved with non-pharmacology, there is no need for pharmacology if the management of maternal acceptance comes from counseling and family support is sufficient and successful. This case, of course, requires support and assistance from a psychiatrist or psychologist if it has entered the moderate/severe category. Keywords: anxiety, depression, IUFD.